Effect of Various Annealing Temperature on Microstructure and Properties of Metastable β-Type Ti-35Nb-2Ta-3Zr Alloy for Biomedical Applications - Ma, Fengcang; Zhang, Gaojie; Liu, Ping; Chen, Juan; Liu, Xinkuan; Li, Wei (Frontiers in Materials, 2020)
Abstract: Microstructure and properties of a metastable β-type Ti-35Nb-2Ta-3Zr alloy after cold rolling plus annealing at various temperatures were investigated systematically. The X-ray diffraction results show that the sample annealed at 923 K is mainly composed of the β phase (92.3%). However, the samples annealed at 723 K, 823 K and 1023 K contain a large amount of α″ phase of 39.6%, 36.5%, and 39.4%, respectively. The elastic modulus of the sample annealed at 923 K is about 50.1 Gpa. However, these of the samples annealed at 723 K, 823 K, and 1023 K are 73.7 GPa, 56.1 GPa and 70.2 GPa. Furthermore, the sample annealed at 923 K presents the best elasticity and the highest recovery strain (~66.87%). The corrosion rate of the sample annealed at 923 K (~2.403µm·a-1) is the lowest among all the samples, which may be attributed to its minimum content of α″ phase.